Regulating Place : Standards and the Shaping of Urban America. - Eran Ben-Joseph (Taylor & Francis, 2005)
Tracing how codes arose when they did, and how they were adapted over time, the authors examine the increasing influence of regulatory codes over urban design and planning in the past century.